Portfolio entrepreneurship in farming: Empirical evidence from the 1881 census for England and Wales. (October 2017) - Radicic, Dragana; Bennett, Robert; Newton, Gill
Highlights: Whole population analysis based on census. Farm size, population density and farmers' age are non-linear with probability of pluriactivity. Low levels of regional variation. Victorian married couple offered the most frequent means to share resources, and family members opened opportunities for additional business development. Urban market opportunities encouraged increased portfolio development as density increased in fringe urban areas.